Hepatic abscess: a rare complication after liver transplant. Issue 10 (5th September 2016) - Kornasiewicz, Oskar; Hołówko, Wacław; Grąt, Michał; Gorski, Zuzanna; Dudek, Krzysztof; Raszeja‐Wyszomirska, Joanna; Krawczyk, Marek
Abstract: Background: This study was conducted to evaluate the predisposing factors, microbiology, treatment, and outcomes associated with hepatic abscess, a rare but serious complication which may accur after an orthotopic liver transplant (OLT). Methods: This was a retrospective study based on a prospectively maintained database of 1100 patients who underwent OLT at the Medical University of Warsaw. An abscess was defined on imaging as solitary or multiple localized parenchymal collections in patients with clinical signs of infection, with or without positive cultures from blood or abscess aspirate. Results: Fifteen patients (1.4%) developed hepatic abscess, including 12 (80%) with multiple abscesses. Predisposing factors included biliary pathology (eight patients), hepaticojejunostomy (six patients), and hepatic artery stenosis or thrombosis (five patients). Ten patients were treated using multiple percutaneous and endoscopic interventional procedures in addition to antimicrobial treatment whereas five were treated solely with antibiotics. Five patients (33.3%) died due to multi‐organ failure secondary to abscess treatment, including one unsuccessful case of re‐OLT. Thirteen patients (87%) had bacterial growth and five (33.3%) had fungal growth in their blood or abscess aspirates. Conclusions: Hepatic abscess after liver transplantation may be treated successfully with percutaneous and endoscopic intervention, along with antibiotics according to the results of microbial cultures of blood and/or abscess aspirates.